An Unfulfilled Promise? Higher Education Quality and Professional Underemployment in Peru - Gustavo Yamada; Pablo Lavado; Joan J. Martínez (Institute for the Study of Labor (IZA), 2015)
Despite the high growth of the Peruvian economy during the last decade, college graduates are facing increasing difficulties to find occupations that match their higher educational background, skills and educational investments. This scenario is embodied in the "professional underemployment" condition by which 4 out of 10 college graduates, by 2012, are overeducated, occupying non-professional and sub-paid positions. We propose that the deterioration in higher education quality has been a trigger for the increase in underemployment of university graduates, as an alternative to the literature that analyzes its causes related to labor demand. The main objective is to explore and quantify the extent to which higher education quality contributes to professional underemployment in Peru. Using data from the National Household Survey for the period 2004-2012 and the National University Census for the years 1996 and 2010, we propose a discrete choice model that measures the impact of college quality on the individual condition of underemployment in the long run. The source of variability for identifying this effect is the institutional and legal process of deregulation of universities initiated in the nineties. Our results indicate that the probability of being underemployed among graduates who attended "lower quality" universities increased from 0.19 to 0.30 beginning the college market deregulation. These estimation consider a twofold effect of deregulation, over the quality of university to which university applicants are prone to attend and in the probability of acquiring university education among individuals with lower academic skills.
Keywords: C21; J23; J24; J44; J64; 330; discrete choice models; employment determination; occupational choice; human capital; professional labor markets and occupation; unemployment